2015
DOI: 10.1016/j.socscimed.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Concussion under-reporting and pressure from coaches, teammates, fans, and parents

Abstract: Concussions from sport present a substantial public health burden given the number of youth, adolescent and emerging adult athletes that participate in contact or collision sports. Athletes who fail to report symptoms of a suspected concussion and continue play are at risk of worsened symptomatology and potentially catastrophic neurologic consequences if another impact is sustained during this vulnerable period. Understanding why athletes do or do not report their symptoms is critical for developing efficaciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
283
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 304 publications
(296 citation statements)
references
References 74 publications
11
283
2
Order By: Relevance
“…College students who perceived pressure from their parents to continue playing while experiencing the symptoms of an SRC were less likely to report a suspected future SRC. 64 Understanding how this pressure is communicated between parents and athletes and how the nature of this communication changes by sport context and athlete age is an important direction for future investigation. For example, Kroshus et al 64 suggested that pressure from some parents may not be communicated directly but that athletes internalize the investment parents have made and infer parental reporting preferences.…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…College students who perceived pressure from their parents to continue playing while experiencing the symptoms of an SRC were less likely to report a suspected future SRC. 64 Understanding how this pressure is communicated between parents and athletes and how the nature of this communication changes by sport context and athlete age is an important direction for future investigation. For example, Kroshus et al 64 suggested that pressure from some parents may not be communicated directly but that athletes internalize the investment parents have made and infer parental reporting preferences.…”
Section: Interpersonal Levelmentioning
confidence: 99%
“…These could include perceptions about what stakeholders in the athletic environment other than teammates, such as coaches or parents want them to do when it comes to concussion reporting. Recent research conducted with the same sample of athletes finds that the more stakeholders from whom an athlete experiences pressure to continue play while symptomatic after a concussion the less likely they are to intend to report symptoms of a future concussion [65]. Other explanations could include nonrelational expectancies about concussion reporting such as perceptions about whether or not reporting E. Kroshus et al…”
Section: Social Norms and Concussionmentioning
confidence: 99%
“…15,16 The Centers for Disease Control's Heads Up concussion education program states, "It is better to miss one game than the whole season." 17 However, due to many factors, including the culture of sports (ie, play through injury), 18,19 poor awareness of SRC signs/symptoms, 20, 21 and limited access to medical professionals, an estimated 50% to 70% of concussions go unreported/ undetected. 20,22,23 In fact, in 2013, the Institute of Medicine and National Research Council stated that the culture of sports negatively influences SRC reporting and that athletes, coaches, and parents do not fully acknowledge the risks of playing while injured.…”
mentioning
confidence: 99%